PENDAMPINGAN IMPLEMENTASI KEMITRAAN PENANGKARAN BENIH PADI DALAM PRODUKSI BENIH BERSERTIFIKAT DI CV MAYANGSARI AGRO SEED JEMBER - Aliya, Hilda Rahma; Kusumaningrum, Anisa Dewi; Dinullah, Pandu Satrio; Novikarumsari, Nurul Dwi (Department of Agronomy, Faculty of Agriculture, University of Jember, 2026)
Certified rice seed production is an important effort to support the availability of high-quality seeds in improving food crop productivity. CV Mayangsari Agro Seed, Jember Regency, implements a rice seed breeding partnership system involving the company and partner farmers in production activities, quality control, and the provision of certified seeds. However, the success of this partnership system requires integrated management to ensure that each production stage is carried out according to certified seed production at CV Mayangsari Agro Seed. The activity was carried out through student involvement in various stages, including observation of cultivation processes, assistance in crop quality monitoring, field inspection activities, seed sampling, post-harvest handling, and seed management. The result showed that the implemented partnership system was able to integrate the roles of the company as a provider of production facilities, technical guidance, and production management with the roles of Farmers as cultivation actors who followed established standards. This assistance activity contributed to supporting production process regularity, improving understanding of seed quality standards, and strengthening the partnership relationship between the company and seed breeder Farmers. This activity was expected to serve as a model for implementing a seed production partnership system that supports the sustainability of certified rice seed availability